Optimization of Strain Gauge Transducer for Weighing Application Using GRA Method - Kolhapure, Rakesh; Shinde, Vasudev; Kamble, Vijay (Asian Journal of Engineering and Applied Technology, 2015)
The main objective of current research is optimization of strain gauge transducer used in weighing application by maximizing sensitivity and minimizing volume. A simple model of strain gauge based ‘Double Ended Shear Beam’ transducer is considered for Finite Element Analysis (FEA). Taguchi method has been applied to construct an orthogonal array based on selected parameters. Next, multiobjective optimization is performed. As Taguchi method is unable to perform multi-objective optimization combined approach of Taguchi and Grey Relational Analysis (GRA) is carried out. This combined approach gives optimum parametric combination based on highest Grey Relation Coefficient (GRC). Analysis of Variance (ANOVA) is statistical technique is used to investigate contribution of each process parameters on the performance characteristic.